Bio-Medical Waste Management - Sahai, Sushma (New Delhi : APH Publishing Corporation, 2009)
Contributed articles.
Bibliography references & Indixing
Keywords: College of Fort St. George (Madras, India); Madras (India) -- Intellectual life -- 19th century